Quantitative Analysis of Micro-CT Imaging and Histopathological Signatures of Experimental Arthritis in Rats - Matthew D. Silva; Anneli Savinainen; Rasesh Kapadia; Jason Ruan; Elizabeth Siebert; Nicole Avitahl; Rebecca Mosher; Karen Anderson; Bruce Jaffee; Lisa Schopf; Sudeep Chandra (Molecular Imaging)
Micro-computed tomographic (micro-CT) imaging provides a unique opportunity to capture 3-D architectural information in bone samples. In this study of pathological joint changes in a rat model of adjuvant-induced arthritis (AA), quantitative analysis of bone volume and roughness were performed by micro-CT imaging and compared with histopathology methods and paw swelling measurement. Micro-CT imaging of excised rat hind paws ( n = 10) stored in formalin consisted of approximately 600 30-μm slices acquired on a 512 × 512 image matrix with isotropic resolution. Following imaging, the joints were scored from H&E stained sections for cartilage/bone erosion, pannus development, inflammation, and synovial hyperplasia. From micro-CT images, quantitative analysis of absolute bone volumes and bone roughness was performed. Bone erosion in the rat AA model is substantial, leading to a significant decline in tarsal volume (27%). The result of the custom bone roughness measurement indicated a 55% increase in surface roughness. Histological and paw volume analyses also demonstrated severe arthritic disease as compared to controls. Statistical analyses indicate correlations among bone volume, roughness, histology, and paw volume. These data demonstrate that the destructive progression of disease in a rat AA model can be quantified using 3-D micro-CT image analysis, which allows assessment of arthritic disease status and efficacy of experimental therapeutic agents.